Pertumbuhan Morganella morganii pada cakalang dengan kondisi penyimpanan berbeda dan deteksi histamin metode TLC: Pertumbuhan Morganella morganii pada cakalang dengan kondisi penyimpanan berbeda dan deteksi histamin metode TLC - Ratnawati, Susana Endah; Sari, Lutfia Permata; Agustyar, Ahmad Awaludin; Puspita, Indun Dewi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Morganella morganii, a strong histamine-producing bacterium (HPB), has been frequently detected in seafood, such as skipjack tuna. Temperature fluctuations and improper packaging have resulted in bacterial proliferation and histamine production. This study aimed to determine the effects of different packaging and temperature conditions on M. morganii growth and to examine histamine formation in skipjack tuna. A factorial design with two factors, namely packaging type (vacuum and non-vacuum) and storage temperature (4, 15, 30, and 40°C), was used in this study.  The bacterial growth model over time was analyzed using DMFit software. Histamine production was analyzed using thin-layer chromatography (TLC) combined with ImageJ program visualization. The results indicated that different temperatures significantly affected the bacterial growth rate (p < 0.05). The application of vacuum packaging at 4 °C retarded histamine formation in skipjack tuna cubes. The highest growth rate (0.2652 log CFU-1h-1) was observed in samples under non-vacuum packaging stored at 40 °C. M. morganii. At 15 °C, a 3 to 4 log increase was observed, starting from 3.2 to 7.5 (vacuum packaging) and from 5.8 to 8.3 log CFU-1 mL-1 (non-vacuum packaging) at the end. Nevertheless, the production of histamine in vacuum-packed samples stored at 15°C after days 3 and 4 of incubation were 446 ppm and 443.5 ppm, respectively. These findings highlight the importance of proper packaging of skipjack tuna using a cold chain system during storage. This study also confirmed the potential application of TLC for the detection of histidine and histamine.